Reframing Professional Identity: Professional Development Framework for Learning/Educational Designers - Pingo, Zablon; Laudari, Suman; Sankey, Michael (Journal of University Teaching and Learning Practice, 2024)
This paper develops the conversation focused on what professional competencies and skills learning design professionals (LDs) have or need to develop to meet contemporary learning design professional demands in organisations and learning institutions. In this paper, we used the lens of lifelong learning theory and skill analytics approach to develop a professional framework for learning design professionals. As people transition into thirdspace professional spaces like educational or learning design, a professional development framework can act as a reflective tool to support workplace learning and identity framing to look backward and forward to achieve personal and professional goals. A framework like this can potentially guide and support learning design teams and individuals to reflect on what skills they possess and identify gaps to plan how to address skill gaps through professional development, workplace learning and networking opportunities